2013
DOI: 10.1583/13-4372.1
|View full text |Cite
|
Sign up to set email alerts
|

Chimney and Periscope Grafts Observed Over 2 Years After Their Use to Revascularize 169 Renovisceral Branches in 77 Patients With Complex Aortic Aneurysms

Abstract: PURPOSE: To evaluate the performance of periscope and/or chimney grafts (CPGs) in the endovascular treatment of pararenal or thoracoabdominal aneurysms using off-the-shelf devices. METH-ODS: Between February 2002 and August 2012, 77 consecutive patients (62 men; mean age 73±9 years) suffering from pararenal aortic (n=55), thoracoabdominal (n=16), or arch to visceral artery aneurysms (n=6) were treated with aortic stent-graft implantation requiring chimney and/or periscope grafts to maintain side branch perfusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
95
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(95 citation statements)
references
References 22 publications
0
95
0
Order By: Relevance
“…The chimney technique has been applied and presented promising outcomes to extend the proximal landing zone during the endovascular repair of thoracic aortic aneurysms [8][9][10][11]. However, in aortic dissections, this technique might be substantially different from that in aneurysm repairs owing to anatomical and pathophysiologic differences.…”
Section: Introductionmentioning
confidence: 99%
“…The chimney technique has been applied and presented promising outcomes to extend the proximal landing zone during the endovascular repair of thoracic aortic aneurysms [8][9][10][11]. However, in aortic dissections, this technique might be substantially different from that in aneurysm repairs owing to anatomical and pathophysiologic differences.…”
Section: Introductionmentioning
confidence: 99%
“…In presented case we did not decide to use it due to longitudinal size of the aneurysm [14]. Moreover, multicentre study of Lachat et al [21] showed that 25% of patients who had above-mentioned techniques, at the time of discharge had endoleaks type I and III. Though during follow-up most of the leaks thrombosed spontaneously, it was considerable risk of postoperative rupture of 11-cm aneurysm in early period.…”
Section: Discussionmentioning
confidence: 89%
“…Additional visceral vessels were addressed in nine (69%) of these patients with chimney/periscope graft 14,15 (13 vessels), Viabahn Open Revascularization Technique 16 (2 vessels), and end-to-side anastomosis (2 vessels; Fig 1).…”
Section: Resultsmentioning
confidence: 99%